Using Of Binders in The Production of Briquettes - Kobilov Kh.X.; Sharipova N.R. (Periodica Journal, 2023)
The adverse effect of the use of fossil fuels on the environment and public health has given rise to a sustained renewable energy research and development. An important component of global renewable energy mix is the use of loose biomass, including agricultural and forestry residues, to produce solid fuels in the form of briquettes. Briquettes play a significant role in bioenergy mix in developing and developed countries. The production of biomass briquettes often entails the collection, transportation, storage, processing, and compaction of loose biomass that meet specific quality parameters. The densification process often involves the addition of binders to improve the cohesive strength of the briquette material. This paper surveys recent literature from 2012 to 2021 to establish the current state of research on the use of binders in briquette production; and reviews current parameters used in assessing the quality of biomass briquettes with focus on mechanical and handling properties. While a number of quality parameters were identified, their assessment methodologies varied widely in the literature, thus necessitating standardization for comparability purposes. The review also includes factors affecting the wide production and adoption of biomass briquettes in most developing economies and proposes ways of overcoming the bottlenecks
Keywords: densification; binders; briquettes